Unplugged coding applications - Başaran, Mehmet; Talan, Tarik; Çakmak, Furkan; Doğan, Yunus; Batdi, Veli (Nova Science Publishers, Inc., 2024)
Coding is an electronic language used for software development and issuing commands on computers. Generally, it refers to managing computer hardware, enabling computers to perform tasks and operations. Advancements in computer and internet technologies have made many tasks and operations controllable in the virtual world, significantly facilitating human life. Eliminating distances for communication, conducting spending and shopping online, and the evolution of remote education are just a few examples of the benefits brought about by coding, which involves issuing commands to computers. Nations and corporations now require individuals with these skills to keep up with developments and strengthen their positions. In recent years, there has been a noticeable increase in programs aimed at imparting coding skills to individuals. Studies indicate that commencing coding education at an early age enables students to learn about computers and working methods earlier, proving more beneficial for skill development. Many European countries are now including coding education in their curriculum at early ages. Additionally, coding education enhances students' computational thinking, critical thinking, and problem-solving skills. Hence, countries aspiring for development need to prioritize this education. Coding and coding education can be conducted in different types depending on age and educational level. Non-computer-based coding, often used in preschool, primary school, and beginner levels, includes block-based coding, text-based coding, and robotic coding. Non-computer-based coding aims to increase interest in computer science and teach coding concepts. This approach, also known as "Computer Science Unplugged," consists of activities designed to concretize computer logic and coding terms, making them easier for individuals to understand. Non-computer-based coding is imparted to students using various methods such as kinesthetic activities, role-playing activities, puzzle activities, artistic activities, and curiosity-driven activities. Through this education, students gain preliminary knowledge about how commands are given on computers, how visuals are created, the binary number system, how commands are sequenced, error detection and correction processes, search and sorting processes, encryption, and shortest path selection, among many other topics. The choice of non-computer-based coding activities is made considering the students' developmental levels. These activities aim to arouse curiosity in students and provide an enjoyable atmosphere during applications. It is also crucial for the facilitating teacher to relate these activities to computers and coding, explaining this connection to the students. © 2024 Nova Science Publishers, Inc. All rights reserved.
Keywords: Coding; Coding education; Non-computer-based coding; Unplugged coding